A newly recognized fossil coelacanth highlights the early morphological diversification of the clade - Friedman, M; Coates, M (2006)
Previously considered an actinopterygian or an osteichthyan incertae sedis, the Devonian (Givetian-Frasnian) Holopterygius nudus is reinterpreted as a coelacanth. This genus is among the oldest coelacanths known from articulated remains, but its eel-like morphology marks a considerable departure from the conventional coelacanth body plan. A cladistic analysis places Holopterygius as the sister taxon of the Carboniferous (Serpukhovian) genus Allenypterus. Despite the specialized morphology of these genera, they occupy a surprisingly basal position in coelacanth phylogeny; only Diplocercides and Miguashaia are further removed from the crown. A morphometric analysis reveals that coelacanths were anatomically disparate early in their history. Conflicts between this result and those of previous studies challenge the adequacy of systematic character sets for describing historical patterns of morphological variety. Coelacanths have long had an iconic place in the study of vertebrate evolution for their apparent anatomical conservatism over geological time, but Holopterygius provides clear evidence for rapid morphological evolution early in the history of this clade. © 2005 The Royal Society.